Iron-based amorphous composite magnetic powder core and preparation method

By ball milling and edge grinding of FeSiBC amorphous powder, combined with an improved pressing process, the problem of limited improvement in soft magnetic properties of magnetic powder cores in the prior art is solved, and a magnetic powder core with high permeability, low loss and stable performance is achieved.

CN119889910AActive Publication Date: 2025-04-25NANCHANG UNIV

Patent Information

Application Number
CN202510387478.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-04-25
Estimated Expiration
2045-03-31

AI Technical Summary

Technical Problem

The prior art fails to fully consider the relationship between the orientation of amorphous powder and the performance of the composite magnetic powder core, resulting in limited improvement in the soft magnetic performance of the magnetic powder core.

Method used

By ball milling the FeSiBC amorphous powder, nanocrystals are generated, and the edges and corners of the powder are polished to improve the insulation performance. Combined with the improved pressing process, two press molding and vacuum impregnation and pressure impregnation resin solution are used to ensure sliding and insulating properties between the powders.

Benefits of technology

The high permeability, low loss, stability with frequency and high DC bias performance of the magnetic powder core is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119889910A_ABST
    Figure CN119889910A_ABST
Patent Text Reader

Abstract

The invention provides an iron-based amorphous composite magnetic powder core and a preparation method, and belongs to the technical field of power electronics, and the preparation method comprises the following steps: carrying out ball milling on FeSiBC amorphous flaky powder; feSiBC amorphous flaky powder obtained after ball milling and FeSiBCCr amorphous spherical powder are mixed according to a certain proportion, mixed powder is obtained, and the mass of the FeSiBC amorphous flaky powder accounts for 85%-90% of the total mass of the mixed powder; the mixed powder is put into a phosphoric acid solution to be subjected to passivating treatment; the passivated mixed powder is put into a mold to be subjected to preliminary compression molding, and a preformed body is obtained; and carrying out vacuum infiltration and pressure infiltration on the preformed body with a resin solution, baking, putting into a mold, and carrying out final compression molding, so as to obtain the product. The prepared magnetic powder core has high magnetic conductivity, low loss, stability along with frequency change and high direct current bias performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of power electronics, and in particular relates to an iron-based amorphous composite magnetic powder core and a preparation method thereof. Background Art

[0002] With the increasing development of power electronics and communication technology, amorphous soft magnetic alloys have become important research materials due to their excellent magnetic properties, and soft magnetic powder cores are one of their application areas. Compared with silicon steel and ferrite, soft magnetic powder cores have high saturation magnetization, high magnetic permeability and low loss, and are a medium- and high-frequency soft magnetic composite material that fills the gap between low and high frequencies.

[0003] According to the shape, amorphous soft magnetic powder can be divided into flake powder and spherical powder. Flake amorphous powder shows significant potential in electromagnetic applications due to its unique shape and microstructural characteristics, and has gradually become a research hotspot in academic and industrial fields in recent years. Spherical amorphous powder is usually prepared by air-water combined atomization process, and the particle size distribution is relatively uniform and regular. This kind of powder can provide better magnetic uniformity when preparing magnetic powder cores. Flake powder can more easily form an optimized magnetic flux path during the pressing process due to its large surface area to volume ratio. The advantage of this structure may lead to higher magnetic permeability and lower loss of magnetic cores prepared by flake powder, especially in high-frequency applications. Therefore, understanding the performance differences between spherical and flake powders in the preparation of magnetic powder cores, and exploring the microscopic mechanisms behind these differences, are of great significance for the optimization and application of amorphous soft magnetic materials.

[0004] In the prior art, the Chinese invention patent with the announcement number CN112908604B discloses an iron-based amorphous composite magnetic powder core and a preparation method thereof, wherein the composite powder after insulation coating is pressed into a mold, and after stress relief annealing, the iron-based amorphous composite magnetic powder core is obtained. This technical solution improves the soft magnetic properties of the magnetic powder core by increasing the density and microcrystallization, but does not consider the relationship between the orientation of the flaky powder and the performance of the composite magnetic powder core, so the improvement of the soft magnetic properties of the magnetic powder core is limited. Summary of the invention

[0005] In order to solve the above problems, the present invention provides an iron-based amorphous composite magnetic powder core and a preparation method thereof. By ball milling FeSiBC amorphous sheet-like powder, deformation-induced nanocrystals are generated, and the edges and corners of the flaky powder are polished, the insulation performance between the powders is improved, and combined with the improved pressing process, the prepared magnetic powder core has high magnetic permeability, low loss, stability with frequency changes, and high DC bias performance.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows: On the one hand, the present invention provides a method for preparing an iron-based amorphous composite magnetic powder core, comprising: ball-milling FeSiBC amorphous sheet-shaped powder; mixing the ball-milled FeSiBC amorphous sheet-shaped powder with FeSiBCCr amorphous spherical powder in a certain proportion to obtain a mixed powder, wherein the mass of the FeSiBC amorphous sheet-shaped powder accounts for 85%-90% of the total mass of the mixed powder; placing the mixed powder in a phosphoric acid solution for passivation treatment; placing the passivated mixed powder in a mold for preliminary pressing to obtain a preform; vacuum-impregnating and pressure-impregnating the preform with a resin solution, baking, placing the preform in a mold for final pressing to obtain the preform.

[0007] Furthermore, the average particle size of the FeSiBC amorphous sheet-like powder before ball milling is 80 μm-110 μm, and the ratio of the average particle size of the FeSiBCCr amorphous spherical powder to the FeSiBC amorphous sheet-like powder before ball milling is 1:(3.5-4.5).

[0008] Furthermore, the average particle size of the FeSiBC amorphous sheet-like powder before ball milling is 90 μm-100 μm.

[0009] Furthermore, the ball milling process is: maintaining a rotation speed of 50r / min-80r / min for 10min-20min; maintaining a rotation speed of 90r / min-120r / min for 5min-10min.

[0010] Furthermore, before the passivation treatment, the mixed powder is cleaned, and the cleaning process is: soaking the mixed powder in an alkaline solution with a pH of 8-9 for at least 20 minutes; secondly, soaking in an acidic solution with a pH of 5-6 for at least 5 minutes; after completion, washing with deionized water.

[0011] Furthermore, the passivation process is as follows: immersion treatment is performed using an aqueous solution of phosphoric acid and sodium nitrate, wherein the volume concentration of phosphoric acid is 12%-16%, the volume concentration of sodium nitrate is 2%-5%, and the rest is deionized water; during the immersion process, the pH is maintained at 2-3, the temperature is 60°C-80°C for passivation for 10min-20min, and then the temperature is 30°C-40°C for passivation for 10min-20min, and the passivation process is stirred at 50r / min-60r / min, and then cleaning is performed after completion.

[0012] Furthermore, the preliminary pressing process is: placing the mixed powder after passivation into a mold and pressing it at a pressure of 0.8 GPa-1.0 GPa.

[0013] Furthermore, the vacuum infiltration and pressure infiltration processes are as follows: evacuate to a vacuum degree not exceeding 0.2 Pa, pour in the resin solution, and maintain for at least 10 minutes; then, apply a pressure of at least 5 MPa to the system and maintain for at least 10 minutes.

[0014] Furthermore, the final pressing pressure is 1.5 GPa-2.0 GPa.

[0015] On the other hand, the present invention provides an iron-based amorphous composite magnetic powder core, which is prepared by the above-mentioned preparation method.

[0016] The beneficial effects brought by the technical solution provided by the embodiment of the present invention include: (1) The present invention ball-mills FeSiBC amorphous sheet powder. First, the sharp edges of the amorphous sheet powder are impacted and blunted to avoid subsequent puncture of the insulating coating layer. Second, the relatively blunted positions, i.e., the positions with a curvature greater than 1 mm, are hammered to induce the generation of nanocrystals on the powder surface. In particular, the nanocrystals are generated on the powder surface, thereby improving the magnetic coupling between the amorphous matrix and the nanocrystals, increasing the magnetic permeability of the prepared magnetic powder core, and reducing the loss. Finally, the formation of nanocrystals facilitates the sliding between the FeSiBC amorphous sheet powder and the FeSiBCCr amorphous spherical powder in the subsequent preforming process, so that the long axis of the amorphous sheet powder is arranged in a certain orientation, thereby avoiding puncture of the insulating layer during the sliding process, and improving the soft magnetic properties of the magnetic powder core.

[0017] (2) In order to improve the sliding effect between FeSiBC amorphous sheet-like powder and FeSiBCCr amorphous spherical powder, the present application limits the mass ratio of the two. If the content of FeSiBC amorphous sheet-like powder is high, the sliding is poor and it is difficult to form an arrangement with a certain orientation. If the content of FeSiBC amorphous sheet-like powder is low, that is, the content of FeSiBCCr amorphous spherical powder is high, the degree of aggregation of the amorphous spherical powder will increase, thereby reducing the soft magnetic properties of the magnetic powder core.

[0018] (3) The pressing process is defined, and two pressing processes are adopted. The initial pressing process takes into account the sliding between the FeSiBC amorphous sheet-shaped powder and the FeSiBCCr amorphous spherical powder, so that the two slide to the desired orientation. During the sliding process, the passivation film passivated with phosphoric acid solution is likely to break. Based on this consideration, the gaps between the powders or the broken passivation film gaps are filled by vacuum infiltration and pressure infiltration of resin solution, thereby improving the strength of the magnetic powder core while ensuring the insulation performance; secondly, compared with the one-step pressing process of the prior art, the filling amount of the resin solution is reduced and the density of the magnetic powder core is improved. Specifically, resin needs to be added in the early stage of the one-step pressing process. During the direct pressing process, there is a problem that the internal resin cannot be effectively discharged, resulting in a low density of the prepared magnetic powder core. The present application makes the prepared preform have a passage for filling the resin solution by adjusting the powder mass ratio and the sliding relationship, thereby reducing the filling amount of the resin solution and improving the density of the magnetic powder core. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0020] Figure 1 A schematic diagram of an iron-based amorphous composite magnetic powder core prepared according to an embodiment of the present invention; Figure 2 The SEM images of the amorphous powders provided in Example 1 of the present invention, a is the FeSiBC amorphous sheet-shaped powder after ball milling, and b is the FeSiBCCr amorphous spherical powder; Figure 3 This is an EDS P element distribution detection diagram of the mixed powder after passivation treatment provided in Example 1 of the present invention, a is FeSiBC amorphous sheet-shaped powder, and b is FeSiBCCr amorphous spherical powder; Figure 4 A side profile of the iron-based amorphous composite magnetic powder core provided in Example 1 of the present invention; Figure 5 A side profile of the iron-based amorphous composite magnetic powder core provided in Example 2 of the present invention; Figure 6 This is a side profile of the iron-based amorphous composite magnetic powder core provided in Comparative Example 1 of the present invention; Figure 7 A graph showing the relationship between the magnetic permeability and frequency of the iron-based amorphous composite magnetic powder core provided in the embodiments and comparative examples of the present invention; Figure 8A graph showing the relationship between the density of the iron-based amorphous composite magnetic powder core and the amount of FeSiBCCr amorphous spherical powder added provided in the embodiments and comparative examples of the present invention; Fig. 9 This is a graph showing the relationship between the loss and frequency of the iron-based amorphous composite magnetic powder core provided in the embodiments and comparative examples of the present invention. DETAILED DESCRIPTION

[0021] The present invention is further described in detail below by specific embodiments. However, it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If specific techniques or conditions are not specified in the examples, they are carried out according to the techniques or conditions described in the literature in this area or according to the product instructions. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0022] As used herein, the words "comprises," "including," "having," or any other variations thereof, are intended to cover a non-exclusive inclusion. For example, a process, method, article, or apparatus that includes listed elements is not necessarily limited to those elements but may include other elements not expressly listed or inherent to such process, method, article, or apparatus. The singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise.

[0023] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, any methods, equipment, and materials of the prior art that are similar or equivalent to the methods, equipment, and materials in the embodiments of the present invention may be used to implement the present invention, based on the prior art mastery of those skilled in the art and the description of the present invention.

[0024] Without further explanation, in the embodiments of the present invention, each process is carried out at room temperature, and the measurement is in terms of mass percentage or mass content.

[0025] The present invention provides a method for preparing an iron-based amorphous composite magnetic powder core, comprising: S1, ball milling the FeSiBC amorphous sheet powder; S2, mixing the ball-milled FeSiBC amorphous sheet-shaped powder and the FeSiBCCr amorphous spherical powder in a certain proportion to obtain a mixed powder, wherein the mass of the FeSiBC amorphous sheet-shaped powder is 85%-90% of the total mass of the mixed powder, for example, 85%, 86%, 87%, 88%, 89%, 90%; S3, placing the mixed powder into a phosphoric acid solution for passivation treatment; S4, placing the passivated mixed powder into a mold for preliminary pressing to obtain a preform; S5, vacuum impregnating and pressure impregnating the preform with a resin solution, baking the preform, and placing the preform in a mold for final compression molding to obtain the preform.

[0026] The invention ball-mills FeSiBC amorphous sheet powder. Firstly, the sharp edges and corners of the amorphous sheet powder are impacted and passivated to avoid subsequent puncturing of an insulating coating layer. Secondly, the relatively passivated positions, that is, the positions with a curvature greater than 1 mm, are hammered to induce the generation of nanocrystals on the powder surface. In particular, the nanocrystals are generated on the powder surface, thereby improving the magnetic coupling effect between the amorphous matrix and the nanocrystals, improving the magnetic permeability of the prepared magnetic powder core, and reducing the loss. Finally, the formation of the nanocrystals facilitates the sliding between the FeSiBC amorphous sheet powder and the FeSiBCCr amorphous spherical powder in the subsequent preforming process, so that the long axis of the amorphous sheet powder is arranged in a certain orientation, thereby avoiding puncturing of the insulating layer during the sliding process, and improving the soft magnetic properties of the magnetic powder core. In order to improve the sliding effect between FeSiBC amorphous sheet-like powder and FeSiBCCr amorphous spherical powder, the present application limits the mass ratio of the two. If the content of FeSiBC amorphous sheet-like powder is high, the sliding is poor and it is difficult to form an arrangement with a certain orientation. If the content of FeSiBC amorphous sheet-like powder is low, that is, the content of FeSiBCCr amorphous spherical powder is high, the degree of aggregation of the amorphous spherical powder will increase, thereby reducing the soft magnetic properties of the magnetic powder core. The pressing process is defined, and two pressing processes are adopted. The initial pressing process takes into account the sliding between the FeSiBC amorphous sheet-shaped powder and the FeSiBCCr amorphous spherical powder, so that the two slide to the desired orientation. During the sliding process, the passivation film passivated with a phosphoric acid solution is likely to break. Based on this consideration, the gaps between the powders or the broken passivation film gaps are filled by vacuum infiltration and pressure infiltration of resin solutions, thereby improving the strength of the magnetic powder core while ensuring the insulation performance; secondly, compared with the one-step pressing process of the prior art, the filling amount of the resin solution is reduced and the density of the magnetic powder core is improved. Specifically, resin needs to be added in the early stage of the one-step pressing process. During the direct pressing process, there is a problem that the internal resin cannot be effectively discharged, resulting in a small density of the prepared magnetic powder core. In the present application, the mass ratio of the powder and the sliding motion are adjusted so that the prepared preform has a passage for filling the resin solution, thereby reducing the filling amount of the resin solution and improving the density of the magnetic powder core.

[0027] It should be noted that the baking temperature is based on the temperature required for the resin solution to solidify, which is common knowledge. For illustration, the present invention uses epoxy resin and the baking temperature is 70°C.

[0028] The average particle size of the FeSiBC amorphous sheet-like powder is 80 μm-110 μm, for example, 80 μm, 90 μm, 100 μm, 110 μm, and the ratio of the average particle size of the FeSiBCCr amorphous spherical powder to the FeSiBC amorphous sheet-like powder before ball milling is 1:(3.5-4.5), for example, 1:3.5, 1:4.0, 1:4.5. Through the above definition, the sliding movement ability of the FeSiBC amorphous sheet-like powder and the FeSiBC amorphous sheet-like powder is improved.

[0029] Preferably, the average particle size of the FeSiBC amorphous sheet-like powder is 90 μm-100 μm.

[0030] The ball milling process is: maintaining a rotation speed of 50 r / min-80 r / min for 15 min-30 min.

[0031] Preferably, the ball milling process is: maintaining a rotation speed of 50r / min-80r / min for 10min-20min; maintaining a rotation speed of 90r / min-120r / min for 5min-10min. In the early stage, the sharp parts of the FeSiBC amorphous sheet powder are ground by a small rotation speed to avoid the amorphous sheet powder being broken into smaller particle sizes due to excessive ball milling speed, and at the same time, the surface of the amorphous sheet powder is modified; in the later stage, the ball milling is performed at a larger rotation speed to form nanocrystals in the deeper parts of the powder particles, such as forming nanocrystals at a depth of at least 10nm, so as to improve the integrity and strength of the phosphoric acid passivation film in the subsequent preliminary pressing process.

[0032] Before the passivation treatment, the mixed powder is cleaned, and the cleaning process is as follows: the mixed powder is soaked in an alkaline solution with a pH of 8-9 for at least 20 minutes to remove oil stains and the like from the mixed powder; secondly, the mixed powder is soaked in an acidic solution with a pH of 5-6 for at least 5 minutes to remove oxides on the surface of the powder, so that the prepared passivation film is closely combined with the substrate; after completion, it is cleaned with deionized water.

[0033] The passivation process is as follows: immersion treatment is performed using phosphoric acid and sodium nitrate aqueous solutions, wherein the volume concentration of phosphoric acid is 12%-16%, the volume concentration of sodium nitrate is 2%-5%, and the rest is deionized water; during the immersion process, the pH is maintained at 2-3, the temperature is 60℃-80℃ for passivation for 10min-20min, and then the temperature is 30℃-40℃ for passivation for 10min-20min, and the passivation process is stirred at 50r / min-60r / min, and then the passivation is completed. The passivation reaction is accelerated by adding sodium nitrate as an oxidant, and the pH value of the solution is adjusted by adding ammonia water. A loose passivation film is generated at a higher temperature in the early stage, and then a complete and dense passivation film is generated at a lower temperature. The loose passivation film is conducive to the sliding movement between powders, and the dense passivation film ensures that there is good insulation between powder particles. The passivation time should not be too long, otherwise it will cause part of the film layer to dissolve. Ultrasonic vibration is strictly prohibited in this process. Since a loose passivation film is generated in the early stage, if ultrasonic vibration is used, there is a possibility that the loose passivation film will fall off, and the stirring speed should not be too high.

[0034] The preliminary pressing process is: placing the passivated mixed powder into a mold and pressing it at a pressure of 0.80 GPa-1.0 GPa, preferably maintaining the pressure for at least 5 minutes.

[0035] Preferably, during the pressing process, additional vibration is applied with a vibration frequency of 50Hz-100Hz. The vibration frequency needs to be limited. If the vibration frequency is too small, it will not promote the sliding movement; if the vibration frequency is too high, the additional wear between the powders will increase, reducing the insulation performance between different powder particles.

[0036] The vacuum infiltration and pressure infiltration processes are as follows: evacuate the system to a vacuum degree not exceeding 0.2 Pa, pour in the resin solution, and maintain for at least 10 minutes; then, apply a pressure of at least 5 MPa to the system and maintain for at least 10 minutes.

[0037] The final compression molding pressure is 1.5 GPa-2.0 GPa, and the pressure is preferably maintained for at least 5 minutes.

[0038] The embodiment of the present invention further provides an iron-based amorphous composite magnetic powder core, which is prepared by the above-mentioned preparation method.

[0039] The magnetic powder core prepared by the present invention is a ring-shaped magnetic powder core with an outer diameter of 40 mm, an inner diameter of 24 mm and a height of 21 mm. Figure 1 As shown, the pressing direction is perpendicular to the paper direction.

[0040] For illustration, in the embodiment of the present invention, FeSiBC amorphous sheet powder is Fe 93.1 Si 4.3 B2.4 C 0.2 , FeSiBCCr amorphous spherical powder adopts Fe 85.7 Si 7.9 B 3.6 C 0.8 Cr 2.0 .

[0041] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0042] Example 1

[0043] The embodiment of the present invention provides a method for preparing an iron-based amorphous composite magnetic powder core, and a magnetic powder core prepared by the method, comprising: S1, ball milling the FeSiBC amorphous sheet powder, the ball milling process is: keeping the speed at 50r / min for 15min, the FeSiBC amorphous sheet powder after ball milling is as follows Figure 2 As shown in (a), it can be seen that the FeSiBC amorphous powder after ball milling has rounded edges and corners.

[0044] S2, the ball-milled FeSiBC amorphous sheet-like powder and the FeSiBCCr amorphous spherical powder are mixed in a certain proportion to obtain a mixed powder, wherein the mass of the FeSiBC amorphous sheet-like powder is 85% of the total mass of the mixed powder, and the FeSiBCCr amorphous spherical powder is Figure 2 As shown in (b), the average particle size of the FeSiBC amorphous sheet-like powder is 92.3 μm, and the average particle size of the FeSiBCCr amorphous spherical powder is 23.1 μm.

[0045] S3, placing the mixed powder in a phosphoric acid solution for passivation treatment. After washing the mixed powder, soak it in a phosphoric acid and sodium nitrate aqueous solution, wherein the volume concentration of phosphoric acid is 12%, the volume concentration of sodium nitrate is 2%, and the rest is deionized water; during the soaking process, the pH is maintained at 2.0, the temperature is 60°C for passivation for 10 minutes, and then the temperature is 30°C for passivation for 10 minutes, and the passivation process is stirred at 50r / min. After completion, wash it. Figure 3 (a) and Figure 3 As can be seen in (b), the P element is evenly distributed on the surface of the two amorphous powders to form a uniform insulating layer.

[0046] S4. Put the passivated mixed powder into a mold for preliminary pressing at a pressure of 0.8 GPa to obtain a preform.

[0047] S5. Vacuum impregnate and pressure impregnate the preform with a resin solution, bake it, and then place it in a mold for final compression molding. The vacuum impregnation and pressure impregnation process is as follows: evacuate to a vacuum degree of 0.2Pa, pour in the resin solution, and keep it for 10 minutes; then, apply pressure to the system to 5Mpa, keep it for 10 minutes, and then press it with a pressure of 1.5Gpa. The side view of the prepared magnetic powder core is shown in the figure. Figure 4 As shown, Figure 1 Side view of the magnetic powder core. Figure 4 The upper and lower parts are the force application directions. It can be seen that the FeSiBC amorphous sheet-like powder is arranged along a certain orientation, and the long axis is approximately perpendicular to the pressure direction.

[0048] Example 2

[0049] The embodiment of the present invention provides a method for preparing an iron-based amorphous composite magnetic powder core, and a magnetic powder core prepared by the method, comprising: S1. Ball milling the FeSiBC amorphous sheet powder, wherein the ball milling process is: maintaining a rotation speed of 80 r / min for 30 minutes.

[0050] S2. The ball-milled FeSiBC amorphous sheet-like powder and the FeSiBCCr amorphous spherical powder are mixed in a certain proportion to obtain a mixed powder, wherein the mass of the FeSiBC amorphous sheet-like powder is 90% of the total mass, the average particle size of the FeSiBC amorphous sheet-like powder is 100 μm, and the ratio of the average particle size of the FeSiBCCr amorphous spherical powder to the FeSiBC amorphous sheet-like powder is 1:4.5.

[0051] S3, placing the mixed powder in a phosphoric acid solution for passivation treatment. After washing the mixed powder, soak it in a phosphoric acid and sodium nitrate aqueous solution, wherein the volume concentration of phosphoric acid is 16%, the volume concentration of sodium nitrate is 5%, and the rest is deionized water; during the soaking process, the pH is maintained at 3.0, the temperature is 80°C for passivation for 20 minutes, and then the temperature is 40°C for passivation for 20 minutes, and the passivation process is stirred at 60r / min, and then washed after completion.

[0052] S4. Put the passivated mixed powder into a mold for preliminary pressing at a pressure of 1.0 GPa to obtain a preform.

[0053] S5. The preform is vacuum impregnated and pressure impregnated with a resin solution, and after baking, it is placed in a mold for final compression molding. The vacuum impregnation and pressure impregnation process is as follows: evacuate to a vacuum degree of 0.2Pa, pour in the resin solution, and keep it for 10 minutes; then, apply pressure to the system to 5Mpa, keep it for 10 minutes, and then press it at a pressure of 2Gpa.

[0054] The side view of the prepared magnetic powder core is shown in Figure 5 As shown, it can be seen that the FeSiBC amorphous sheet-like powder is arranged along a certain orientation, and the long axis is approximately perpendicular to the pressure direction.

[0055] Example 3

[0056] The embodiment of the present invention provides a method for preparing an iron-based amorphous composite magnetic powder core, and a magnetic powder core prepared by the method, comprising: S1. Ball milling the FeSiBC amorphous sheet powder, wherein the ball milling process is: maintaining a rotation speed of 50 r / min for 15 minutes.

[0057] S2. The ball-milled FeSiBC amorphous sheet-like powder and the FeSiBCCr amorphous spherical powder are mixed in a certain proportion to obtain a mixed powder, wherein the mass of the FeSiBC amorphous sheet-like powder is 85% of the total mass, the average particle size of the FeSiBC amorphous sheet-like powder is 90 μm, and the ratio of the average particle size of the FeSiBCCr amorphous spherical powder to the FeSiBC amorphous sheet-like powder is 1:3.5.

[0058] S3, placing the mixed powder in a phosphoric acid solution for passivation treatment. After washing the mixed powder, soak it in a phosphoric acid and sodium nitrate aqueous solution, wherein the volume concentration of phosphoric acid is 12%, the volume concentration of sodium nitrate is 2%, and the rest is deionized water; during the soaking process, the pH is maintained at 2.0, the temperature is 60°C for passivation for 10 minutes, and then the temperature is 30°C for passivation for 10 minutes, and the passivation process is stirred at 50r / min, and then washed after completion.

[0059] S4. Put the passivated mixed powder into a mold for preliminary pressing at a pressure of 0.8 GPa to obtain a preform.

[0060] S5. The preform is vacuum impregnated and pressure impregnated with a resin solution, and after baking, it is placed in a mold for final compression molding. The vacuum impregnation and pressure impregnation process is: evacuate to a vacuum degree of 0.2Pa, pour in the resin solution, and keep it for 10 minutes; then, apply pressure to the system to 5Mpa, keep it for 10 minutes, and then press it at a pressure of 1.5Gpa.

[0061] In the prepared magnetic powder core, FeSiBC non-sheet-shaped powder is arranged along a certain orientation, and the long axis is approximately perpendicular to the pressure direction.

[0062] Example 4

[0063] Different from Example 3, in step S2 of this embodiment, the average particle size of the FeSiBC amorphous sheet-like powder is 80 μm, and the ratio of the average particle size of the FeSiBCCr amorphous spherical powder to the FeSiBC amorphous sheet-like powder is 1:4.

[0064] In the prepared magnetic powder core, FeSiBC non-sheet-shaped powder is arranged along a certain orientation, and the long axis is approximately perpendicular to the pressure direction.

[0065] Example 5

[0066] Different from Example 3, in step S2 of this embodiment, the average particle size of the FeSiBC amorphous sheet-like powder is 110 μm, and the average particle size ratio of the FeSiBCCr amorphous spherical powder to the FeSiBC amorphous sheet-like powder is 1:4.

[0067] In the prepared magnetic powder core, FeSiBC non-sheet-shaped powder is arranged along a certain orientation, and the long axis is approximately perpendicular to the pressure direction.

[0068] Example 6

[0069] Different from Example 1, in step S1 of this embodiment, the ball milling process is: maintaining a rotation speed of 50 r / min for 10 min; maintaining a rotation speed of 90 r / min for 5 min.

[0070] In the prepared magnetic powder core, FeSiBC non-sheet-shaped powder is arranged along a certain orientation, and the long axis is approximately perpendicular to the pressure direction.

[0071] Example 7

[0072] Different from Example 1, in step S1 of this embodiment, the ball milling process is: maintaining a rotation speed of 80 r / min for 20 min; maintaining a rotation speed of 120 r / min for 10 min.

[0073] In the prepared magnetic powder core, FeSiBC non-sheet-shaped powder is arranged along a certain orientation, and the long axis is approximately perpendicular to the pressure direction.

[0074] Comparative Example 1 Different from Example 1, in step S2 of this comparative example, the mass of the FeSiBC amorphous sheet-like powder is 95% of the total mass.

[0075] The side view of the prepared magnetic powder core is shown in Figure 6 As shown, it can be seen that the FeSiBC amorphous sheet-like powder is arranged along a certain orientation, and the long axis is arranged at an acute angle to the pressure direction.

[0076] Comparative Example 2 Different from Example 1, in step S2 of this comparative example, the mass of the FeSiBC amorphous sheet-like powder is 80% of the total mass.

[0077] Comparative Example 3 Different from Example 1, step S1 is omitted in this comparative example.

[0078] Comparative Example 4 Different from Example 1, in step S3 of this comparative example, the temperature is 30° C. and the passivation is performed for 20 min.

[0079] Comparative Example 5 Different from Example 1, in step S3 of this comparative example, 1 wt % epoxy resin is added to the mixed powder after passivation, and then the mixed powder is pressed and molded at a pressure of 1.5 Gpa.

[0080] Effect verification Typically, examples 1 and 2 (the results of examples 1 and 2 are similar to those of other examples) are selected, and comparative examples 1 and 2 are used to compare the changes in the magnetic permeability and frequency of the magnetic powder cores prepared from pure FeSiBC amorphous sheet-like powder and pure FeSiBCCr amorphous spherical powder. The results are as follows: Figure 7 As shown, from Figure 7 It can be seen that the magnetic permeabilities of Examples 1 and 2 have no significant change in the frequency range of 0-1000kHz, and the magnetic permeabilities of Examples 1 and 2 are significantly higher than those of Comparative Examples 1 and 2. Figure 8 It can be seen that the density of the composite magnetic powder core increases first and then decreases with the addition of FeSiBCCr amorphous spherical powder. This is because the reasonable mass ratio of FeSiBC amorphous sheet-like powder and FeSiBCCr amorphous spherical powder promotes movement during the pressing process, resulting in a higher density of the prepared magnetic powder core. The increase in the mass ratio of FeSiBCCr amorphous spherical powder leads to severe agglomeration, which reduces the density of the magnetic powder core.

[0081] Select Examples 1 and 2 (the results of Examples 1 and 2 are similar to those of other Examples) and Comparative Examples 1 and 2, the changes in loss and frequency of the magnetic powder cores prepared from pure FeSiBC amorphous sheet-shaped powder and pure FeSiBCCr amorphous spherical powder are shown in the following table. Fig. 9 As shown, from Fig. 9 It can be seen that the losses of Examples 1 and 2 are lower than those of Comparative Examples 1 and 2 in the frequency range of 25-125kHz.

[0082] In order to compare the performance of each embodiment and the comparative example, the magnetic permeability of the amorphous composite magnetic powder core of the present invention is measured under the test conditions of Bm=0.05T, 1-1000kHz; the loss is measured under the test conditions of Bm=0.05T, 1000kHz. The following parameters are tested respectively, and the test results are shown in Table 1.

[0083] Table 1 Soft magnetic properties measurement data of various embodiments and comparative examples

[0084] The above description is only an embodiment of the present application and is not intended to limit the protection scope of the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing an iron-based amorphous composite magnetic powder core, characterized in that: include: The FeSiBC amorphous sheet-like powder was ball-milled; The ball-milled FeSiBC amorphous sheet-shaped powder and the FeSiBCCr amorphous spherical powder are mixed in a certain proportion to obtain a mixed powder, wherein the mass of the FeSiBC amorphous sheet-shaped powder accounts for 85%-90% of the total mass of the mixed powder; placing the mixed powder into a phosphoric acid solution for passivation treatment; The mixed powder after passivation is placed in a mold for preliminary pressing to obtain a preform; The resin solution is vacuum impregnated and pressure impregnated, and then placed in a mold for final compression molding after baking. The passivation treatment process is: immersion treatment is carried out using phosphoric acid and sodium nitrate aqueous solutions, wherein the volume ratio of phosphoric acid is 12%-16%, the volume ratio of sodium nitrate is 2%-5%, and the rest is deionized water; during the immersion process, the pH is maintained at 2-3, the temperature is 60°C-80°C for passivation for 10min-20min, and then the temperature is 30°C-40°C for passivation for 10min-20min, and the passivation process is stirred at 50r / min-60r / min, and cleaning is performed after completion.

2. The preparation method according to claim 1, characterized in that: The average particle size of the FeSiBC amorphous sheet-like powder before ball milling is 80 μm-110 μm, and the ratio of the average particle size of the FeSiBCCr amorphous spherical powder to the FeSiBC amorphous sheet-like powder before ball milling is 1:(3.5-4.5).

3. The preparation method according to claim 2, characterized in that: The average particle size of the FeSiBC amorphous sheet powder before ball milling is 90 μm-100 μm.

4. The preparation method according to claim 1, characterized in that: The ball milling process is: maintaining a rotation speed of 50r / min-80r / min for 10min-20min; maintaining a rotation speed of 90r / min-120r / min for 5min-10min.

5. The preparation method according to claim 1, characterized in that: Before the passivation treatment, the mixed powder is cleaned, and the cleaning process is as follows: soaking the mixed powder in an alkaline solution with a pH of 8-9 for at least 20 minutes; secondly, soaking in an acidic solution with a pH of 5-6 for at least 5 minutes; after completion, washing with deionized water.

6. The preparation method according to claim 1, characterized in that: The preliminary pressing process is: placing the passivated mixed powder into a mold and pressing it at a pressure of 0.8 GPa-1.0 GPa.

7. The preparation method according to claim 1, characterized in that: The vacuum infiltration and pressure infiltration processes are as follows: evacuate the system to a vacuum degree not exceeding 0.2 Pa, pour in the resin solution, and maintain for at least 10 minutes; then, apply a pressure of at least 5 MPa to the system and maintain for at least 10 minutes.

8. The preparation method according to claim 1, characterized in that: The final compression molding pressure is 1.5 GPa-2.0 GPa.

9. An iron-based amorphous composite magnetic powder core, characterized in that: The iron-based amorphous composite magnetic powder core is prepared by the preparation method described in any one of claims 1-8.

Citation Information

Patent Citations

  • A Ferrous-Based Amorphous Composite Magnetic Powder Core and Its Preparation Method

    CN112908604B

  • Method for preparing iron-based composite magnetic powder core

    CN102637518A

  • Method for manufacturing iron-silicon-aluminium metal magnetic powder core

    CN102938312A

  • Preparation method of circle-oriented non-crystal magnetic powder core

    CN105097167A

  • Preparation method of amorphous or nanocrystalline soft magnetic powder core

    CN106890999A

Cited By

  • High-density mould pressing bonding samarium-iron-nitrogen magnet with extremely low cavity volume ratio and preparation method of high-density mould pressing bonding samarium-iron-nitrogen magnet

    CN120126917A